Rothmund-Thomson syndrome - Popadić, S. (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2006)
We report two unusual patients with Rothmund-Thomson syndrome (RTS), a rare genodermatosis. The first patient is a 5-year-old girl with congenital poikiloderma, photosensitivity, plantar punctate keratoderma, stunted growth and severe mental retardation. Plantar keratoderma associated with RTS has been reported only once. The second patient is a 21-year-old female presentingwith rounded "moon" face, trunk obesity, coeliac disease, short stature and mild mental retardation. This is the first case of RTS associated with coeliac disease.
Keywords: Celiac Disease; Celiakija; Comorbidity; dermatologija; Keratoderma, Palmoplantar; Keratodermija palmoplantarna; kožne bolezni; Poikiloderma Congenitale; Poikilodermija prirojena; Soobolevnost